Fatigue life of a carbon fiber composite T-joint under a standard fighter aircraft spectrum load sequence. (1st September 2015) - Thawre, M.M.; Pandey, K.N.; Dubey, A.; Verma, K.K.; Peshwe, D.R.; Paretkar, R.K.; Jagannathan, N.; Manjunatha, C.M.
Abstract: The carbon fiber/epoxy composite (CFC) T-joints were fabricated and tested to determine their fatigue life under a standard fighter aircraft spectrum load sequence, mini-FALSTAFF with various reference loads. Further, the fatigue life of T-joint subjected to the same spectrum load sequence was predicted. For this purpose, the static pull-out (tension) and push-in (compression) tests were conducted on T-joints. Then, the constant amplitude fatigue tests were conducted to determine the load-life (P–N) curves at three different load ratio, R = P min / P max of 0.1, −1.0 and 10.0.The static and fatigue test data generated was then employed to construct constant life diagram (CLD) for T-joint. The fatigue damage for each of the rain flow counted load cycle of mini-FALSTAFF spectrum load sequence was determined using CLD. Using linear damage accumulation theory, the fatigue life of T-joint was estimated. The predicted fatigue life was observed to agree quite well with experimental results.